APD-Containing Cyclolipodepsipeptides Target Mitochondrial Function in Hypoxic Cancer Cells. Issue 11 (15th November 2018) - Jacobsen, Kristian Mark; Villadsen, Nikolaj Lilholm; Tørring, Thomas; Nielsen, Camilla Bak; Salomón, Trine; Nielsen, Morten Muhlig; Tsakos, Michail; Sibbersen, Christian; Scavenius, Carsten; Nielsen, Rikke; Christensen, Erik Ilsø; Guerra, Paula Fernandez; et al.
Summary: The natural product family of macrocyclic lipodepsipeptides containing the 4-amido-2, 4-pentadienoate functionality possesses intriguing cytotoxic selectivity toward hypoxic cancer cells. These subpopulations of cancer cells display increased metastatic potential and resistance to chemo- and radiotherapy. In this paper, we present studies on the mechanism of action of these natural products in hypoxic cancer cells and show that this involves rapid and hypoxia-selective collapse of mitochondrial integrity and function. These events drive a regulated cell death process that potentially could function as a powerful tool in the fight against chemo- and radiotherapy-resistant cancer cells. Toward that end, we demonstrate activity in two different mouse tumor models. Graphical Abstract: Highlights: APD-CLDs induce a rapid loss of mitochondrial ultrastructure and function Toxicity is mechanistically distinct from other hypoxia-activated compounds APD-CLD-induced cell death is dependent on oxygen concentration The APD-CLDs are potently active in vivo Abstract : Hypoxic cancer cells constitute a major challenge in chemo- and radiotherapy and demand the development of hypoxia-selective drugs. Here, Jacobsen et al. present comprehensive biological evaluation of a natural product family that induces selective cell death in hypoxic cancer cells by rapidly impeding mitochondrial function.